Comparison of presentations to the emergency department during the COVID-19 pandemic (COPED-C). (9th March 2021) - Kociejowski, A; Hobart, C; Jina, R; Aberman, I; Backhurst, E; Beaumont, A; Crompton, J; Sneep, R; Cantle, F; Dodhia, H
Abstract: Background: Concerns have been raised that patients requiring emergency care may not have accessed healthcare services during coronavirus disease 2019 (COVID-19) lockdown. Methods: This case control study aimed to understand changes in characteristics and diagnosis of patients attending a large UK Emergency Department (ED) during the first wave of the COVID-19 pandemic (March–May 2020) compared with equivalent weeks in 2019. Results: We found a 50.7% drop in first attendances to the ED in 2020. Likelihood of attendance and admission decreased for paediatric patients and increased for patients ≥ 46 years, and for men. Likelihood of admission increased for all Black ethnic groups and for patients from the most deprived index of multiple deprivation quintiles. This shift to an older, male, more deprived patient population with greater representation of ethnic minority groups was amplified in the 'Infections' diagnostic category. Conclusions: COVID-19 has dramatically impacted ED usage. Our analysis contributes to local resource planning and understanding of changes in healthcare-seeking behaviour during the pandemic. Future research to identify positive behaviour changes could help sustain a reduction in non-urgent visits in the longer term.